2022
DOI: 10.1242/jcs.256008
|View full text |Cite
|
Sign up to set email alerts
|

TLE4 regulates muscle stem cell quiescence and skeletal muscle differentiation

Abstract: Muscle stem (satellite) cells express Pax7, a key transcription factor essential for satellite cell maintenance and adult muscle regeneration. We identify the corepressor Transducin-Like Enhancer of Split-4 (TLE4) as a Pax7 interaction partner expressed in quiescent satellite cells under homeostasis. A subset of satellite cells transiently downregulate TLE4 during early time points following injury. We identify these to be activated satellite cells where TLE4 downregulation is required for Myf5 activation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Functional annotation within KEGG pathways showed that it is involved in Wnt and Notch signaling pathways. As a prominent regulator of the canonical Wnt signaling pathway (GO: 0016055) and cellular biosynthetic process (GO: 0031326), TLE4 was recently suggested to regulate muscle satellite cell quiescence and muscle differentiation by repressing PAX7-mediated MYF5 transcriptional activation in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional annotation within KEGG pathways showed that it is involved in Wnt and Notch signaling pathways. As a prominent regulator of the canonical Wnt signaling pathway (GO: 0016055) and cellular biosynthetic process (GO: 0031326), TLE4 was recently suggested to regulate muscle satellite cell quiescence and muscle differentiation by repressing PAX7-mediated MYF5 transcriptional activation in mice [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLE4 supresses Pax7-mediated Myf5 transcriptional activation through inducing Myf5 enhancer to continue latency. Loss of TLE4 function results into Myf5 upregulation thus, showing its role in growth through transcription suppression 29 . TLE4 is also a critical regulator in haematopoiesis 30 and bone development 31 .…”
Section: Discussionmentioning
confidence: 99%
“…10 TLEs have been shown to play important roles in myogenesis. 11,15 Numerous studies suggest that TLEs interact with homeodomain proteins to repress target genes. 10 Since Zeb1 is a homeodomain protein, we hypothesized that it may interact with TLEs.…”
Section: Zeb1 Inhibits Myhc-embryonic Expression and Muscle Different...mentioning
confidence: 99%
“…Transducin‐like Enhancer of Split (TLE) proteins are a family of corepressors with vital functions during embryonic development, adult homeostasis and regeneration 10 . Recently, we found that Tle4 prevents Pax7‐mediated activation of myogenic factor 5 ( Myf5 ) in quiescent muscle stem cells 11 . Tle3 has been shown to be important in promoting white adipose tissue and mitochondrial gene expression 12–14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation